Efficient Resource Scheduling in Cloud Computing (International Journal of Advanced Research in Computer Science, 2017)
Cloud Computing offers elastic, scalable, resource sharing services by using resource management. Resource monitoring and prediction are the keys to achieve resource utilization with high-performance management in cloud computing. Resource scheduling is one of the major issue of cloud computing, the scheduling policy and algorithm affect the performance of cloud system directly. In recent years, Cloud Computing offers high-performance computing capacity, which reminds cloud providers to utilize resource fully because of the limitation of resources. This research paper aims to monitor the resources available in cloud using Hidden Markov Model (HMM). The proposed model is used for resource monitoring and then the resource will be classified based on Less, Average, and Heavy loaded categories as the availability of the resources and the appropriate scheduling algorithm will be selected on demand, the efficiency of algorithm has been calibrated using different kind of workload scenario. Keywords: Cloud Computing, High Performance, Resource Classifier, Utilization, Hidden Markov Model (HMM)